Fanatisme Mazhab dalam Perspektif Fikih Kontemporer: Analisis Konseptual dan Implikasinya terhadap Kehidupan Sosial Keagamaan - Aripin Marpaung; Muhammad Zakwan Roji; Adnan Zuhdi Silalahi; Nur Ade Amelia Oktobery; Nur Fadilah; Muhammad Arif Rahman Hakim (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
Islam, which fundamentally promotes unity and tolerance, has historically accommodated a plurality of Islamic jurisprudential schools (mazhab) formed through scholarly legal reasoning (ijtihad). However, contemporary Muslim societies increasingly experience school-based fanaticism, manifested in rigid allegiance to a particular school of thought and the delegitimization of alternative interpretations. Despite its prevalence, this phenomenon remains insufficiently examined within the framework of contemporary Islamic jurisprudence. This study aims to conceptualize school-based fanaticism and to analyze its dimensions, characteristics, underlying causes, and socio-religious impacts. Employing a qualitative library-based research design, this study systematically examines classical and contemporary Islamic legal sources using a comparative and analytical approach. The findings demonstrate that school-based fanaticism operates at both individual and collective levels and is characterized by epistemic rigidity, absolutist truth claims, and tendencies toward social fragmentation. The study identifies several contributing factors, including limited engagement with authoritative Islamic scholarship, the amplifying role of unregulated digital media, and political instrumentalization of jurisprudential differences. While its impacts are predominantly negative—such as heightened sectarian tension and weakened communal cohesion—this study also acknowledges a constructive potential when school adherence is grounded in ethical scholarship and intellectual discipline. Overall, the study emphasizes the importance of strengthening religious literacy, promoting jurisprudential moderation (wasatiyyah), and fostering respect for interpretive diversity as strategic responses to school-based fanaticism in contemporary Islamic societies.